2013
DOI: 10.1016/j.respol.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Modularity, interfaces definition and the integration of external sources of innovation in the automotive industry

Abstract: In the last two decad es, the au to industr y has shown a steady increase of vehicle development outsourcing and a shift of both pr oduct developm ent tasks and knowledge from car makers to suppliers. This trend has increased the interest toward product m odularity as a tool to suggest that they may work as substitutes and are rather difficult to combine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 56 publications
(49 reference statements)
2
74
1
5
Order By: Relevance
“…However, modular development requires contextual knowledge to interconnected parts. Contrary to earlier expectations of complexity outsourcing, (Cabigiosu et al 2013) states that "modular design does not substitute for high-power interorganizational coordination mechanisms". This supports the current change, especially in research and development departments, towards interdisciplinary and transdisciplinary departments, such as e.g.…”
Section: Transdisciplinary Research For Automotive Multi-operating Symentioning
confidence: 76%
“…However, modular development requires contextual knowledge to interconnected parts. Contrary to earlier expectations of complexity outsourcing, (Cabigiosu et al 2013) states that "modular design does not substitute for high-power interorganizational coordination mechanisms". This supports the current change, especially in research and development departments, towards interdisciplinary and transdisciplinary departments, such as e.g.…”
Section: Transdisciplinary Research For Automotive Multi-operating Symentioning
confidence: 76%
“…Several empirical studies indicate that knowledge plays an important role in the relationship between product modularity and the degree of inter-organizational integration (Brusoni et al, 2001;Cabigiosu et al, 2013;Sanchez & Mahoney, 1996). In this respect Brusoni et al's study (2001) in the aircraft industry shows that systems integration firms that maintain a knowledge base that covers the whole product system are more effective in coordinating the design and manufacturing activities within their network of specialized subsystem suppliers.…”
Section: Architectural and Component Knowledge Moderating The Productmentioning
confidence: 99%
“…Prencipe (2000) also argued that a deep understanding of components' inner working helped manufacturers of aircraft engine control systems to specify, assess, test and integrate components that are externally sourced. Later studies found that in many cases modularity (in the form of standard interfaces) did not per se eliminate the need for buyer-supplier integration (Cabigiosu & Camuffo, 2012a;Cabigiosu et al, 2013;Colfer & Baldwin, 2010). Despite attempts to modularize systems, modularization is unlikely to fully eliminate and/or codify all the interdependencies between subsystems and companies ex ante (Cabigiosu & Camuffo, 2012a;Colfer & Baldwin, 2010;Ethiraj & Levinthal, 2004;Staudenmayer et al, 2005).…”
Section: Architectural and Component Knowledge Moderating The Productmentioning
confidence: 99%
See 2 more Smart Citations